Words have bounded width in SL(n, Z). (July 2019) - Avni, Nir; Meiri, Chen
Abstract : We prove two results about the width of words in SL_n(Z) . The first is that, for every n3, there is a constant C(n) such that the width of any word in SL_n(Z) is less than C(n) . The second result is that, for any word w, if n is big enough, the width of w in SL_n(Z) is at most 87.